2003
DOI: 10.1211/002235702522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic pharmacokinetics of baicalin and baicalein in rats

Abstract: Isoteoline is a compound of aporphine structure derived from the alkaloid glaucine. Previous studies with isoteoline have shown antagonistic activity at 5-HT(2C) serotonergic receptors. We have investigated whether isoteoline interacts with 5-HT(1B) receptors. An isolation-induced social behavioural deficit test in mice was used as a model of stimulation of these receptors. The deficit in the behaviour of isolated mice in this experimental procedure was reported to be sensitive to 5-HT(1B)-receptor stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 27 publications
5
135
1
1
Order By: Relevance
“…Following both types of administration, the levels of free fisetin in serum declined rapidly while the levels of sulfated/glucuronidated fisetin increased. Following oral administration at 50 mg/kg, the serum concentration of fisetin sulfates/glucuronides was maintained at *10 lM for [24 h. These results are in sharp contrast to those obtained for 5 OH and 7 OH flavone [80] and baicalein [48] where the levels of free and conjugated flavonoid never exceeded 1 lM following oral administration. When tested in an assay for antioxidant activity, the fisetin sulfates/glucuronides showed somewhat reduced but still significant activity as compared to free fisetin [80].…”
Section: Metabolism Of Fisetinmentioning
confidence: 58%
“…Following both types of administration, the levels of free fisetin in serum declined rapidly while the levels of sulfated/glucuronidated fisetin increased. Following oral administration at 50 mg/kg, the serum concentration of fisetin sulfates/glucuronides was maintained at *10 lM for [24 h. These results are in sharp contrast to those obtained for 5 OH and 7 OH flavone [80] and baicalein [48] where the levels of free and conjugated flavonoid never exceeded 1 lM following oral administration. When tested in an assay for antioxidant activity, the fisetin sulfates/glucuronides showed somewhat reduced but still significant activity as compared to free fisetin [80].…”
Section: Metabolism Of Fisetinmentioning
confidence: 58%
“…Recent research has reported that baicalin and wogonoside are insoluble in water and hard to be absorbed. However, it is found that baicalein and wogonin are the metabolites of baicalin and wogonoside respectively and can easily be absorbed by digestive tract and its bioavailability is also better than baicalin and wogonoside (Che et al, 2001;Lai et al, 2003). In addition, more scholars found that baicalein and wogonin show strong anti-cancer activities on different kind of cancers cells, such as ovarian, ESCC, bladder, oral, colon, pancreatic, breast, bronchial, colorectal, glioma, lung, cervical cancer cells and the activities are better than baicalin (Zhao et al, 2010;Lan et al, 2011;Huang et al, 2012;Cheng et al, 2012;Zhang et al, 2013;Yang et al, 2013) .…”
Section: Baicalein and Wogoninmentioning
confidence: 99%
“…Earlier pharmacokinetic studies of baicalein in rats have shown that plasma levels of baicalein are low in cases of oral administration as compared to intravenous administration [15]. It is also known that baicalein is absorbed faster and to a greater extent in the intestine [16]. In the rat jejunal loop model, baicalein has also been shown to be readily absorbed [17].…”
Section: Introductionmentioning
confidence: 99%